An examination of works for wind band and woodwind choir: Brasiliana by Joao Guilherme Ripper, Irish tune from county Derry by Percy Grainger and arranged by Frank Erickson, and Celtic hymns and dances by Eric Ewazen - Brooks, Darren S. (Kansas State University, 2008)
This document is based on the preparation, rehearsal, and performance of selected pieces for the Graduate Conducting Recital of Darren S. Brooks. The pieces examined in the theoretical and historical analysis for this report are Brasiliana by Joao Guilherme Ripper, Irish Tune from County Derry by Percy Grainger and arranged by Frank Erickson, and Celtic Hymns and Dances by Eric Ewazen. This document also contains rehearsal plans and procedures for the preparation of the literature. The recital was performed on March 12, 2008 in McCain Auditorium on the campus of Kansas State University, and was performed by the members of the Kansas State University Symphony Band.
Keywords: Celtic Hymns and Dances; Irish Tune from County Derry; Brasiliana; Education, Music (0522)